Economic impacts of applying EU animal protection regulations in hog breeding farms - Balogh, Péter; Ertsey, Imre; Nagy, Lajos (Acta Agraria Debreceniensis, 2001)
Hungary’s intention to join the EU makes it necessary to adopt, introduce and use the EU system of law. In Hungary, the legal control of animal welfare has improved (XXVIIIth law in 1998); however, most of our pig farms do not meet the EU animal welfare law requirements for some reason. We examined 9 pig farms in Hajdú-Bihar, Borsod-Abaúj-Zemplén and Heves counties. We chose those farms which use the combined breeding technology most frequently used in Hungary. The most important part of the welfare directive is the definition of the minimum space per animal. We analysed the data in comparison with EU laws. On the basis of the analysis, it can be said that there is a narrow cross-section: the breeding of piglets. During the cost analysis, we analysed cost and highlighted the permanent cost. We studied how these costs would change if EU animal welfare laws were observed. We also examined the specific data per 1 sow and per 1 kilogram of slaughter pig. We compared the present data (1999) with those we get if EU animal welfare laws concerning minimal space per pig were now followed. It can be stated that after decreasing the sow live-stock in accordance with EU directives, the permanent cost would increase by 17,7% per sow. If the required space per sow were provided, the total cost per sow would increase by 1,9% from 421,1 thousand forints to 429 thousand forints, on average. This would mean a decrease of 7,9 thousand forints profit per sow. As with the decrease of the number of sows, the number of slaughter pigs also decreases. Total cost per 1 kg of slaughter pig would increase from 214,7 forints to 218,2 on average.